Supervised interprofessional student pain clinic program - efficacy with the utilization of zoom - Dao, Brandon; Cao, Ling (Frontiers in Pain Research, 2023)
Introduction Current medical education curriculum on pain management is extremely insufficient even though chronic pain is so prevalent within patient populations. The Supervised Student Inter-professional Pain Clinic Program (SSIPCP) aims to train healthcare professional students to improve their abilities in chronic pain management in interprofessional (IP) teams. Due to the COVID-19 pandemic, Zoom was employed to allow the program to continue. In this study, survey data from students who participated during and before the COVID-19 pandemic were compared to determine if the program carried out via Zoom can maintain its efficacy. Methods Student pre- and post-program survey data were entered into Microsoft Excel spreadsheet and then graphed and analyzed with Sigma Plot. Surveys assessed knowledge in chronic pain physiology and management, attitude towards IP practice, and perceived team skills in the form of questionnaires and open-ended questions. Paired t-tests and Wilcoxon Signed-rank tests were used for two-group comparisons and two-way repeated ANOVA followed by the Holm-Sidak post-hoc tests were used for multiple group comparisons. Results Overall, students continued to exhibit significant improvement in major areas assessed even with the use of Zoom. Strengths of the programs were also shared across student cohorts regardless of Zoom usage. However, despite their improvements, students who utilized Zoom stated that they would have preferred in-person program activities. Conclusion Although students prefer in-person activities, the SSIPCP successfully trained healthcare students in chronic pain management and working in an IP team through Zoom.